Zambia : 2013 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Information Annex highlights that safeguards assessments of the Bank of Zambia (BoZ) were completed in June 2004, January 2009, and October 2010. The 2009 assessment concluded that the bank had adequate safeguards in several areas, but confirmed the existence of certain vulnerabilities in the BoZ's legal framework and financial reporting. The 2010 update report concluded that the BoZ had made progress in implementing safeguards recommendations. The IMF staff noted improvements in the internal audit and internal control mechanisms. Weak statutory independence remains a substantive safeguards concern. Further, Zambia continues to maintain an exchange restriction, which is subject to IMF approval under Article VIII, arising from limitations imposed by the government on access to foreign exchange for the making of payments and transfers for current international transactions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet